Patient responsiveness as a safewards fidelity indicator: a qualitative interview study on an acute psychiatric in-patient ward - Veikko Pelto-Piri; Lars Kjellin; Gabriella Backman; Karoline Carlsson; Anna Björkdahl (BMC, 2024)
Abstract Background The Safewards model aims to reduce conflict and use of containment on psychiatric wards. To evaluate the implementation of Safewards and understand why it is effective in some settings but not in others, it is important to assess the level of implementation fidelity. To do this, the Safewards Fidelity Checklist (SFC) is often used, which focuses on objective visual observations of interventions but does not include patient responsiveness. The latter is a key indicator of implementation fidelity and includes engagement, relevance, acceptability and usefulness. The aim of the present study was to investigate the fidelity of Safewards implementation on an acute psychiatric ward from the perspective of patient responsiveness. Method The study was conducted on a ward for patients with mainly affective disorders. To assess the general level of fidelity the SFC was used together with a detailed ward walkthrough. Ten patients were interviewed with a focus on patient responsiveness to each of the seven interventions implemented on the ward. Data were analysed using qualitative descriptive analysis. Results The findings indicate high implementation fidelity, which was reflected in the SFC assessment, walkthrough and patient responsiveness. Patients gave examples of improvements that had happened over time or of the ward being better than other wards. They felt respected, less alone, hopeful and safe. They also described supporting fellow patients and taking responsibility for the ward climate. However, some patients were unfamiliar with a ward where so much communication was expected. Several suggestions were made about improving Safewards. Conclusions This study confirms previous research that patient responsiveness is an important factor for achieving fidelity in a prevention programme. The patients' descriptions of the acceptability, relevance and usefulness of the specific interventions reflected to a high degree the objective visual observations made by means of the SFC and ward walkthrough. Patient engagement was demonstrated by several suggestions about how to adapt the interventions. There is potential to obtain valuable input from patients when adapting Safewards in practice. This study also presents many examples of practical work with these interventions and the effects it can have on patients' experiences of care.